A Research on the Control System of High-Speed Homopolar Motor with Solid Rotor Based on Flywheel Energy Storage. (17th July 2020) - Jing, Lili; Yu, Yandong; Xue, Xiaochuan
Abstract : In view of the defects of the motors used for flywheel energy storage such as great iron loss in rotation, poor rotor strength, and robustness, a new type of motor called electrically excited homopolar motor is adopted in this paper for flywheel energy storage. Compared to general motors, this motor has the advantages of simple structure, high rotor strength, and low iron loss in rotation. A double closed-loop PI governing system of the new motor was designed, modeled, and simulated with this motor as the controlled object on simulation platform. The simulation result shows that the PI-controlled electrically excited homopolar motor system realized fast speed governing and good system performance, achieved the purpose of quick charge by flywheel energy storage, verified the correctness and effectiveness of the design scheme, and provided data reference and theoretical basis for the practice of future flywheel energy storage experiments.